Genre Parameters of a Narrating as a Document of the Mid-18th Century in the Aspect of Creating a Linguistic Corps - E. M. Sheptukhina (Научный диалог)
The relevance of the study is determined by the need to create linguistic corps of little accessible historical acts sources stored in regional archives. The material for the work was the foundation of the Mikhailovsky village ataman of the State Archive of the Volgograd Region (SAVR, fund 332, inventory 1, files 1-158, 1734-1837). The genre variety of the documents of the fund determines the development of criteria for their genre parameterization, on the basis of which meta-marking can be carried out, which automates the processing of the entire array of sources and searches for linguistic information based on their metadata. In order to determine the speech markers of the document genre for its automatic recognition in the corpus, the narrating of the mid-18th century were parametrized, which were the documents containing information on investigative matters. The speech means of expressing the parameters determined by the communicative situation and correlated with the document form are identified: name, addresser, addressee, function, structure, nature of the transmitted information, spatio-temporal localization of the document. The variability of the speech embodiment of the narrating form is shown. The self-name of the document in combination with a demonstrative or possessive pronoun and verbs expressing a communicative action are defined as speech markers of the genre for meta-marking: this very narrating, they gave this very narrating, they told it with their own narrating.